Study on effectiveness of air-horn device for bird deterrent in paddy cultivation area - Mohd Zaidi, Sidek; Muhammad Afiq Miqhail, Johari (Penerbit UMP, 2022)
Pest birds that have adapted well in paddy cultivation area create problems to rice farmers. Among sound-based bird deterrent device, air-horn could be used since it generates high sound intensity. This study is conducted to evaluate performance of portable air-horn in open-area test condition conducted. This study successfully identifies three dominant pest birds in Pekan’s paddy cultivation area i.e lesser whistling-duck (itik belibis), white-headed munia (pipit uban) and barn swallow (walet). Other than that, site test for portable air-horn device shows that air horn able to produce around 100 dBA sound level. It is enough to frighten bird over 40 metre during daytime and reduce to 20 metre during a night. Further investigation on birds response on different sound quality and setting are still needed for thorough understand for best solution of the pest birds problem in paddy cultivation area.